Mongameli Mabona : his life and work - Wolff, Ernst (Leuven University Press, 2020)
Mongameli Anthony Mabona (1929) is a singular South African scholar with an exceptional life path. The history of British imperialism and apartheid shaped the world into which he was born. To a large extent, these powers had his destiny carved out for him. Nevertheless, a curious set of coincidences enabled him to obtain a tertiary education as a priest, to pursue his doctoral studies in Italy and to befriend Alioune Diop. He is one of the first published philosophers of Anglophone Africa and holds doctorates in theology and anthropology. His opposition to institutionalised racism? including co-authoring the 1970 'Black Priests' Manifesto' - eventually led to his exile. This book documents his life and offers a synoptic reading of his scholarly and poetic work.